Elemental imaging approach to assess the ability of subaerial biofilms growing on constructions located in tropical climates as potential biomonitors of atmospheric heavy metals pollution. (December 2022) - Gallego-Cartagena, Euler; Morillas, Héctor; Morgado-Gamero, Wendy; Fuentes-Gandara, Fabio; Vacca-Jimeno, Víctor; Salcedo, Isabel; Madariaga, Juan Manuel; Maguregui, Maite
Abstract: Over the last decades, the concern about air pollution has increased significantly, especially in urban areas. Active sampling of air pollutants requires specific instrumentation not always available in all the laboratories. Passive sampling has a lower cost than active alternatives but still requires efforts to cover extensive areas. The use of biological systems as passive samplers might be a solution that provides information about air pollution to assist decision-makers in environmental health and urban planning. This study aims to employ subaerial biofilms (SABs) growing naturally on façades of historical and recent constructions as natural passive biomonitors of atmospheric heavy metals pollution. Concretely, SABs spontaneously growing on constructions located in a tropical climate, like the one of the city of Barranquilla (Colombia), have been used to develop the methodological approach here presented as an alternative to SABS grown under laboratory conditions. After a proper identification of the biocolonizers in the SAB through taxonomic and morphological observations, the study of the particulate matter accumulated on the SABs of five constructions was conducted under a multi-analytical approach based mainly on elemental imaging studies by micro Energy Dispersive X-ray fluorescence spectrometry (μ-EDXRF) and Scanning Electron Microscopy coupled with Energy Dispersive X-ray spectrometry (SEM-EDS) techniques, trying to reduce the time needed and associated costs. This methodology allowed to discriminate metals that are part of the original structure of the SABs, from those coming from the anthropogenic emissions. The whole methodology applied assisted the identification of the main metallic particles that could be associated with nearby anthropogenic sources of emission such as Zn, Fe, Mn, Ni and Ti by SEM-EDS and by μ-EDXRF Ba, Sb, Sn, Cl and Br apart others; revealing that it could be used as a good alternative for a rapid screening of the atmospheric heavy metals pollution. Graphical abstract: Image 1 Highlights: Subaerial biofilms (SABs) for passive biomonitoring studies of air quality in tropical cities. Deposition of metallic PM in SABs growing naturally on buildings from tropical cities. μ-EDXRF and SEM-EDS single point and imaging in SABs to assessment air pollution sources. Analytical methodologies for fast and cost-effective assessment of PM deposited in SABs.